Decomposing sociopreneur model supporting national economic recovery through the development of sustainable halal tourism - Haidar, Abdullah; Herindar, Evania; Syihabudin, Muhammad (Journal of Islamic Economics Management and Business (JIEMB), 2022)
This study analyzes the sociopreneur model that can support national economic recovery through sustainable halal tourism. The method used is a case study of a Sociopreneur Community (Sudut Lombok). By conducting in-depth interviews, the author found that Lombok Corner offers the concept of Responsible Tourism and Ecotourism and is supported by several services collaborating with the surrounding community. In addition, Corner Lombok also has several social programs, where a portion of the profits from the business sector, at least 25% of the net profits of investors, will be allocated to social activities to improve the welfare of the people of East Lombok. This business model is expected to be an example for developing Sustainable Halal Tourism in other places to encourage the development of Indonesian halal tourism, whose benefits can also be felt by the surrounding community.